Contemporary motivational strategies for employees performance - Jegatheesvaran, T. (University of Jaffna, 2019)
Motivation which is the core construct in organizational practice and research plays a critical role in achieving business goals and objectives. Employee motivation reflects the level of energy, commitment, and creativity that an employee brings to its jobs. Motivation strategy is considered as a force that drives the employees towards attaining specific goals and objectives of the organization. Motivation strategies play vital role in enhancing employees’ productivity. A growing body of research reveals that contemporary motivation strategies have stronger influence on employees’ performance. The main argument of this scholarly article is “contemporary motivational strategies have greater impact on employees’ performance”. Contemporary motivation strategies which mostly focus on psychological aspect of employees are typically more effective at motivating employees over the long term. The sub argument of this article is “when there is a significant positive relationship between contemporary motivation strategies and employees’ performance, social recognition and employee involvement in decision making highly influence on employees’ performance than other strategies”. Thorough literature review shows that contemporary motivational strategies–the strong determinants of employees’ performance have significant– positive effect on employees’ performance. Empirical evidence also impressively proves that social recognition and employee engagement are more effective in increasing employees’ performance than other motivation strategies.
Keywords: Contemporary; Motivation; Strategy; Performance